'AM I IN ROME, OR IN AULIS?': JOMMELLI'S CAJO MARIO (1746) AS OPERATIC CAPRICCIO. (March 2016) - FORMENT, BRUNO
ABSTRACT: In contrast to what its title suggests, Niccolò Jommelli's Cajo Mario (Rome, 1746) has little to do with the consul Caius Marius (157–86 BC). Instead, the opera transposes the myth of Iphigenia in Aulis to the Roman Republic, having Marius, his daughter, her lover and her villainous suitor assume the roles of Agamemnon, Iphigenia, Achilles and Ajax respectively. Thus configured, Jommelli's opera held the stage until 1772, enjoying fifteen revivals with most of the original music intact – a record in the composer's oeuvre. This essay seeks to clarify the reasons for that remarkable success. By juxtaposing Jommelli's score and Gaetano Roccaforte's libretto with a set of six paintings by the contemporary artist Antonio Joli (c1700–1777), it aims to show how Cajo Mario shares compositional strategies with a connoisseur's genre in the fine arts: the capriccio . In keeping with Joli's capricci, which all deploy the same structural motif, Cajo Mario incorporates a narrative structure through which the 'parallel universe' of related works imposes itself on the opera's setting and action, making spectators wonder – as a character does in the course of the opera – whether they are gazing at an event from republican Rome or reliving a legend from ancient Greece.